Magnetic molecularly imprinted conducting polymer for determination of praziquantel enantiomers in milk. Issue 12 (14th May 2020) - Nascimento, Tienne Aparecida; Silva, Camilla Fonseca; Oliveira, Hanna Leijoto de; da Silva, Ricky Cássio Santos; Nascimento, Clebio Soares; Borges, Keyller Bastos
Abstract : A new selective adsorbent based on magnetic molecularly imprinted conducting polymer was firstly synthetized and applied to the magnetic solid phase extraction (MSPE) for the determination of PZQ enantiomers in milk samples. Abstract : A new selective adsorbent based on magnetic molecularly imprinted conducting polymer was firstly synthetized and applied to the magnetic solid phase extraction (MSPE) for the determination of PZQ enantiomers in milk samples. The enantioselective separation was performed on a Chiralpak® IB column using mobile phase composed of ultrapure water : tetrahydrofuran : diethylamine (65 : 35 : 0.05, v/v/v). After MSPE optimization, in which a magnetic molecularly imprinted polypyrrole (MMIPPy) was used as adsorbent, the best conditions were: 500 μL of acetonitrile as eluent, 75 mg of MMPPy, 1000 μL of milk sample (pH adjusted to 6.5.). The analyses showed recoveries/relative standard deviation (RSD%) 79.7 ± 2.5 and 81.1 ± 2.2 for ( R )-(−)-PZQ and ( S )-(+)-PZQ, respectively. By computational study carried out on the molecular design of the synthesized MMIPPy, it was found that the formation of four hydrogen bonds and one π–π stacking interaction explain the formation of the PZQ-pyrrole pre-polymerization complex at the molecular level. From the analytical validation, the developed method showed to be linear in the concentration range of 0.01 to 10 μg mL −1, with correlation coefficient larger than 0.98 and RSD% values below 15%. The LOQ obtained was 0.01 μg mL −1 for both enantiomers, with RSD% and relative error below 20%. The method was successfully applied in real sheep milk samples from various local suppliers. Finally, the results showed that MMIPPy in MSPE is an economical, simple and easy-to-perform technique.